Influence of Islamic Religious Education Teachers’ Competence on the Formation of Students’ Religious Character - Yusro, Kurnia; Nurhidayati, Indah; Sholihah, Siti Fathiyatus (ISLAMIKA, 2026)
This study is motivated by the limited research examining the comprehensive role of Islamic Religious Education (PAI) teacher competence, covering pedagogical, personal, social, and professional dimensions in shaping students’ religious character in Islamic school settings, despite its importance for realizing the objectives of Kurikulum Merdeka and the Pelajar Pancasila (Pancasila Student Profile). The study aims to test the effect of PAI teacher competence on the formation of students’ religious character. Using a quantitative explanatory method with a correlational survey design, the sample comprised 34 students from class XI.9 at SMA Al-Islam 1 Surakarta selected through total sampling. Data were collected using a closed-ended questionnaire with a 4-point Likert scale supported by documentation, and were analyzed descriptively and inferentially using SPSS (validity and reliability tests, classical assumption tests, and simple linear regression). The results show that PAI teacher competence has a positive and significant effect on the formation of students’ religious character (b = 0.292; t = 2.484; p = 0.018 < 0.05), with a coefficient of determination R² = 16.2%, indicating that 16.2% of the variance in religious character is explained by teacher competence, while the mean levels of teacher competence and students’ religious character fall within the moderate category (mean X = 32.21; mean Y = 35.15). These findings reinforce social learning theory (Bandura) and character education literature, which emphasize teachers as role models who play a central role in the internalization of religious values, while also indicating the presence of other contextual factors that account for the remaining variance. The study implies the need for ongoing professional development for PAI teachers and recommends further research with larger samples, longitudinal or mixed-methods designs, and the inclusion of family and school climate variables to enrich empirical understanding of the determinants of students’ religious character.